Relationship between mood disturbance and physiological responses to training - Hammer, W. L.; Pierce, E. F.; Pace, J.; McGowan, R. W. (Medicine & Science in Sports & Exercise, 1994)
The global measure on the POMS was compared to self-perceptions on muscle soreness and a variety of measures that indicate training stress. It was found that the POMS score related to both perceptual and clinical measures of skeletal muscle stress. Implication: Swimmers can accurately report when they are stressed. Inadvertently, the stress is indicated by mood behaviors.